THE EFFECT OF THINK ALOUD STRATEGY ON STUDENTS’ READING COMPREHENSION AT THE TENTH GRADE OF SMK SWASTA SITI BANUN - Muhammad Rusli; Anna Leli Harahap; Shopiah Anggraini Rambe; Desi Rahmadhani (Universitas Labuhanbatu, 2022)
This study aims to determine the effect of think aloud strategy on students’ reading comprehension at the tenth grade of smk swasta siti banun. The data collection technique was used to measure students’ learning outcomes in the form of assignment questions carried out on the pretest and posttest. The data analysis technique used is normality test using F test, homogeneity test and hypothesis testing using t test. The hypothesis in this study was tested by t-test at a significant level = 0.05. From the calculation of the data it was seen that t-count > t-table (3,41> 1,67). Thus the null hypothesis is that Ho is rejected and Ha is accepted. From the results, it can be concluded that there is a significant effect of Think Aloud Strategy on Students’ Reading Comprehension at Tenth Grade of SMK Swasta Siti BanunKeywords: Reading comprehension; Think Aloud Strategy; Thinking Hard.